SISTEM PENDUKUNG KEPUTUSAN REKRUTMEN PANITIA PENGAWAS PEMILU KECAMATAN (PANWASCAM) MENGGUNAKAN METODE SMART DI BAWASLU KABUPATEN PONOROGO BERBASIS WEB - Pawindyanto, Aditya Danang; Mashuri, Chamdan; Vitadiar, Tanhella Zein; Sucipto, Hadi (Fakultas Teknologi Informasi, 2025)
General Elections (Pemilu) are a crucial pillar of Indonesian democracy, and their success heavily relies on effective oversight. The District Election Supervisory Committee (Panwascam) plays a vital role in ensuring the integrity of elections at the district level. This research aims to design and implement a Decision Support System (DSS) for the recruitment process of the Panwascam at Bawaslu Ponorogo Regency. The Panwascam selection process often faces challenges due to the large number of applicants, which can make it difficult for the selection team to determine the best candidates according to the established criteria. To overcome these issues, a web-based DSS utilizing the Simple Multi-Attribute Rating Technique (SMART) method was developed. The SMART method was chosen for its ability to analyze and assign weights to various criteria transparently and simply, thereby generating more objective and efficient selection recommendations. The output of this system is a final SMART calculation result that can be used by Bawaslu Ponorogo Regency as a recommendation in the decision-making process for accepting Panwascam members. It is expected that with this SMART-based DSS, the Panwascam selection process can run faster and more accurately, and reduce subjectivity in determining successful candidates. The system's accuracy evaluation shows a Mean Absolute Percentage Error (MAPE) of 0.0048%, confirming a high consistency and reliability between the system's calculation results and manual calculations.